Spontaneous Differentiation of T Follicular Helper Cells in LATY136F Mutant Mice - O’Brien, Sarah A.; Zhu, Minghua; Zhang, Weiguo (Frontiers in Immunology, 2021)
Mice with a mutation at the LAT-PLCγ1 binding site (Y136) have a defect in thymocyte development due to dampened TCR signaling. CD4+ T cells that do reach the periphery are hyper-activated and skewed to Th2. Over time, these mice develop an autoimmune-like syndrome, characterize by overproduction of Th2 cytokines, T cell infiltration into various organs, and B cell activation, isotype switching, and autoantibody production. In this study, we examined IL4 production by CD4+ T cells in the LATY136F mice using the KN2 reporter mice, in which human CD2 expression marks T cells that are actively producing IL4 protein. We showed that these mice had spontaneous Tfh differentiation. Despite the fact that the majority of CD4+ T cells were skewed to Th2 and were GATA3+, only a small subset of them were actively secreting IL4. These T cells were Tfh cells that expressed BCL6 and were localized to B cell-rich germinal centers within the spleen. Interestingly, these Tfh cells expressed high levels of both BCL6 and GATA3. By using LAT conditional knockout mice that inducibly express only the LATY136F allele, we further showed that Tfh cell differentiation was likely the result of defective LAT-PLCγ1 signaling in the periphery. In addition, B cells were required for spontaneous development of Tfh cells and uncontrolled T cell expansion in these mice. Together, these results indicated a novel role for tonic LAT-PLCγ1 signaling in modulating Tfh cell differentiation during development of autoimmune syndrome.